PERSONAL BRANDING PUTERI INDONESIA JAWA TIMUR MELALUI MEDIA SOSIAL INSTAGRAM (Universitas Negeri Surabaya, 2023)
Instagram is one of the social media platforms that continues to experience significant growth in usage in Indonesia, This is particularly important for public figures to reflect how they differentiate themselves both in real life and on social media. As the Puteri Indonesia Jawa Timur, they undoubtedly have their own personal branding. This research is a qualitative descriptive study with a constructivist paradigm, employing a case study method and personal branding theory. Data collection methods used in this research include in-depth interviews, documentation, and observation. The results of this study indicate that all three informants authentically portray their personal branding on their Instagram accounts by demonstrating alignment between what they present on social media and their daily lives. The personal branding they exhibit as Puteri Indonesia Jawa Timur is characterized by authenticity, without image manipulation, and humility. They also engage with their followers not only by showcasing personal branding content but also through question-and-answer features to convey their personal branding messages quickly and easily. Keywords : Personal Branding, Social media, Instagram